A Comprehensive Analysis of Rovibrational CO in the Era of JWST - D. Annie Dickson-Vandervelde; Colette Salyk; Geoffrey A. Blake; Clara Ross; Adwin Boogert; Klaus Pontoppidan (The Astronomical Journal)
We present an analysis of CO rovibrational emission lines in the 183 infrared spectra of nearby Class II objects obtained with the NIRSPEC instrument on the Keck II telescope over the past two decades. The sample includes a broad range of stellar mass (both T Tauri and Herbig Ae/Be) and disk evolutionary states (from full to debris disks). We find that 53% of the sample has CO rovibrational emission lines present in their spectrum with disk/stellar subtype detection rates of 82% for transition disks, 61% for Herbigs, and 77% for classical T Tauri stars. Although there is no discernible difference between T Tauri and Herbig Ae/Be star CO detection rates, the detection of accretion and of CO are statistically correlated in T Tauri stars but not in Herbig Ae/Be objects. Within the sample of T Tauri stars, we find that no weak-line T Tauri stars have CO rovibrational emission lines. We use slab modeling to analyze the density, temperature, and emitting area of the sample. The retrieval results imply that Herbig Ae/Be objects tend to have cooler and larger CO emitting regions than T Tauri stars. We find that the CO emitting area is not a thin ring as defined by temperature, but a ring of varying size, likely dependent on the structure of the disk. We also present guidelines on how to approach CO rovibrational emission lines in JWST spectra and present methods for linking ground-based observations with JWST spectra. This includes line-to-continuum ratio estimates based on stellar mass and accretion rate.